Sugar-dependent selective induction of mouse jejunal disaccharidase activities. - Collins, A J (1989)
1. Sugar-containing diets chosen not to affect intestinal structure or enterocyte turnover have been fed to mice previously maintained on a low carbohydrate diet in order to determine their ability to induce disaccharidase enzymes in the small intestine. 2. Glucose-, fructose- and 3-O-methyl-glucose-containing diets increased sucrase and maltase but not lactase activities in mouse jejunal homogenates. These effects were either absent or negligible in more distal regions of the small intestine. 3. Placing mice on glucose-, fructose- or 3-O-methyl-glucose-containing diets was further shown, by quantitative cytochemistry, to cause a 1.6-, 2.6- and 3.2-fold increase in the initial rate at which alpha-glucosidase activity (sucrase + maltase) appeared in the brush-border membrane of developing enterocytes. 4. The time during which alpha-glucosidase activity increased in enterocyte brush-border membranes fell from 30 h for low carbohydrate fed mice to 21, 19 and 17 h in mice fed glucose, fructose and 3-O-methyl-glucose respectively. Change of diet had no effect on the kinetics of lactase expression by developing enterocytes. 5. Maximal alpha-glucosidase activity detected in enterocyte brush-border membranes is equal to RT, where R is the initial rate of enzyme appearance and T is the time during which this rate operates. The ability of sugars to increase R selectively, but only at the expense of T, defines unexpected limits to the capacity of enterocytes to adapt to changes in luminal nutrition. 6. The above results are discussed in relation to other aspects of enterocyte differentiation recently subjected to quantitative analysis. The need to standardize other aspects of intestinal physiology and redefine the energy content of diets containing non-metabolizable substrates in this type of work is also emphasized.